The skin manifestations in end-stage renal disease patients in Jordan, single-center experience - Mohammad Hassan Al-thnaibat; Heba M. Urabi; Hadeel S. Alkofahi; Ola Mohannad Alshriedeh; Raneem Alshraideh; Hanan Esmadi; Ahmed Sheyyab; Bakri Roumi Jamal; Hanan Khaled Hasan (BMC Nephrology)
Abstract Introduction Patients with end-stage renal disease usually undergo hemodialysis as a way of renal function replacement therapy which comes with a wide array of systemic and cutaneous complications. The aim of this study was to evaluate the most frequent dermatological manifestations including xerosis, pruritis and other nail, hair and oral conditions, as these are a very important aspect to be considered while managing the patients psychological and physical needs to improve their outcomes and quality of life. Methods This retrospective cross-sectional study was performed by selecting 77 patients on hemodialysis based on a certain criteria and data was then collected on a sheet using patients database on Hakeem National E-Health Program, in addition to information from interviews with patients during their hemodialysis sessions after taking an oral informed consent and insuring patients’ privacy. Data was analyzed using IBM SPSS Statistics for Windows, Version 20.0. Findings 83.1% (N = 64) of the participants on hemodialysis presented with one or multiple skin conditions. Generalized xerosis, generalized pruritis, pigmentary alterations and arteriovenous (AV) shunt-associated complications were found in 63.6% (N = 49), 36.4% (N = 28), 16.9% (N = 13) and 7.8% (N = 6) respectively. Terry’s nails (19.5%, N = 15) were also a common nail abnormality along with other nail disorders (18.2%, N = 14). Different oral anomalies were associated with 14.3% (N = 11) of subjects and in 22.1% (N = 17), diffuse scalp hair loss was also identified. Conclusion Cutaneous issues such as xerosis, pruritus, pigmentary changes, and nail abnormalities are prevalent among ESRD patients, reflecting the broader systemic effects of chronic kidney disease. Our findings underscore the urgency of early recognition, comprehensive evaluation, and tailored management strategies to improve the physical and psychological burden on patients. Moving forward, targeted research into the underlying mechanisms and innovative therapeutic approaches is essential to enhance both dermatological outcomes and overall patient well-being.